2011
DOI: 10.1371/journal.pone.0028680
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Cytokine induction in Pandemic H1N1 Influenza Virus Infection Accompanied by Robust Production of IL-10 and IL-6

Abstract: BackgroundThe innate immune system is the first line of defense against viruses by inducing expression of cytokines and chemokines. Many pandemic influenza H1N1 virus [P(H1N1)] infected severe cases occur in young adults under 18 years old who were rarely seriously affected by seasonal influenza. Results regarding host cytokine profiles of P(H1N1) are ambivalent. In the present study we investigated host cytokine profiles in P(H1N1) patients and identified cytokines related to disease severity.Methods and Prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
121
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 21 publications
17
121
1
Order By: Relevance
“…A significant elevation of IL-6, IL-10, and TNF-α levels was observed in H1N1 infected patients. The enhanced cytokine expression during H1N1 virus infection is in concordance with other human studies (Arankalle et al, 2010;Hasegawa et al, 2011;Yu et al, 2011). It has also been reported that IL-6 might act as the mediator in induction of IL-10 production, which leads to disease progression (Yu et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A significant elevation of IL-6, IL-10, and TNF-α levels was observed in H1N1 infected patients. The enhanced cytokine expression during H1N1 virus infection is in concordance with other human studies (Arankalle et al, 2010;Hasegawa et al, 2011;Yu et al, 2011). It has also been reported that IL-6 might act as the mediator in induction of IL-10 production, which leads to disease progression (Yu et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…In general, the innate immune system is the first line of defense against viruses by induction of the expression of cytokines and chemokines (Yu et al, 2011). Cytokine activation usually occurs much earlier than the clinically observable response, and it may play an important role in stimulating an immune response to the H1N1 virus infection (Wen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the levels of an anti-inflammatory cytokine, IL-10, were high in an unimmunized WT group compared to immunized WT and CD47KO groups, suggesting that IL-10 may be required to downregulate excessive lung inflammation in a naive host after infection. In support of our observation, a study suggested that a high IL-10 level may be an indicator of disease progression and severity (46). Defective neutrophil migration was observed in the absence of CD47 expression (13).…”
Section: Discussionsupporting
confidence: 85%
“…21,22 ). There are significant changes in cytokines and chemokines in patients with H1N1 influenza even with mild symptoms 23 . The influenza H1N1 pandemic occurred in 2009, and was associated elsewhere with significantly higher ma- ternal morbidity and mortality 24 .…”
Section: Discussionmentioning
confidence: 99%